Mouse in the axilla: a case series of fibroadenoma in the axillary ectopic breast tissue – a rare entity - Gnanaprakash; Dewangan, Manish (International Surgery Journal, 2025)
Axillary polymastia is a common variant of ectopic breast tissue (EBT) with reported incidence of 2% to 6% in women. EBT can undergo the same physiological and pathological processes as the normally located breast. Though fibroadenoma commonly occurs in the breast, it is rare in the ectopic breast tissue. We report a series of four cases of fibroadenoma in axillary breast tissue over past 10 years in our hospital including a giant axillary fibroadenoma which we claim to be the largest till date in the English literature.